2022
DOI: 10.3390/su142215105
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of DFIG-STATCOM Coordinated P2P Grid Connected System Using RMSProp

Abstract: This research work establishes a relationship between STATCOM and DFIG wind turbines in a transmission network for coordinated operation during grid disturbances. A change in wind gust also produces a variable output nonlinearly, thereby making the system unstable. Assuring bus voltage and proper balance of load angle in all the connected generating stations becomes challenging. Therefore, increasing voltage security at all the lines and further enhancing system stability leads to the placement of STATCOM at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Different topologies of DFIG's are proposed by various researches and all the topologies there is reactive power requirement that need to be met for successful operation of DFIG. To compensate for the reactive power, many researchers [3][4][5][6][7][8][9][10][11][12][13][14][15] have proposed STATCOM at strategic locations in the transmission system or at PCC. A shunt connected STATCOM using vector controlled technique is employed in distribution system for weak connected grid and it was concluded that STATCOM compensated for reactive power requirement effectively during grid faults and sudden load switching OFF conditions [4,5].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Different topologies of DFIG's are proposed by various researches and all the topologies there is reactive power requirement that need to be met for successful operation of DFIG. To compensate for the reactive power, many researchers [3][4][5][6][7][8][9][10][11][12][13][14][15] have proposed STATCOM at strategic locations in the transmission system or at PCC. A shunt connected STATCOM using vector controlled technique is employed in distribution system for weak connected grid and it was concluded that STATCOM compensated for reactive power requirement effectively during grid faults and sudden load switching OFF conditions [4,5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To compensate for the reactive power, many researchers [3][4][5][6][7][8][9][10][11][12][13][14][15] have proposed STATCOM at strategic locations in the transmission system or at PCC. A shunt connected STATCOM using vector controlled technique is employed in distribution system for weak connected grid and it was concluded that STATCOM compensated for reactive power requirement effectively during grid faults and sudden load switching OFF conditions [4,5]. [6] explored the application of STATCOM to overcome of Low Voltage Ride Through issue in DFIG based systems due to internal fault of converters in addition to grid faults.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DFIG can be directly connected to the AC power grid and remain constantly synchronized. This includes the capacity to sustain power electronics devices in wind turbines while controlling the power factor [3], [8], [14]- [16] The most difficult aspect of maximizing a wind farm is creating an accurate model of the wind farm. In addition, a significant number of parameters must be tuned to ensure good and stable interaction between the wind farm and the power grid at the common coupling point (PCC).…”
Section: Introductionmentioning
confidence: 99%
“…STATCOM operates by creating reactive electricity in accordance with system needs. Utilizing STATCOM in a wind energy system can increase system performance and decrease reactive power fluctuations [3], [16]- [18]. This work uses STATCOM compensators to optimize DFIG on wind farms that are gridconnected.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of wind energy, several generators can be used to generate electric current; asynchronous generators [14], synchronous generators [15], DC generators [16], and DFIG [17] can be used. However, DFIG remains the most important and most widely used of these types as a result of its ease of command, low cost, durability, and low maintenance compared to some other generators.…”
Section: Introductionmentioning
confidence: 99%